How Halal Certification and Islamic Ethics Tackle Greenwashing: New Solutions for a Sustainable Economy - Ryan Pratama, Muhammad Afif (Journal Of Middle East and Islamic Studies, 2024)
This research explores the role of halal certification and Islamic ethics in addressing greenwashing within the financial sector. Greenwashing, the practice of exaggerating environmental responsibility, undermines genuine sustainability efforts and trust among consumers and investors. Islamic finance, based on principles of transparency, social justice, and ethical business practices, provides a robust framework to counter such deceptive practices. The study proposes expanding halal certification to incorporate environmental standards, ensuring that companies demonstrate both ethical and sustainable practices. This integrated approach offers a unique solution to combat greenwashing and aligns with broader sustainability goals. By including sustainability in halal certification, the credibility and ethical foundations of Islamic finance can be reinforced. The study highlights the need for interdisciplinary collaboration among financial institutions, regulators, and sustainability experts to promote transparency and accountability, fostering a more sustainable economy.